2008
DOI: 10.1016/j.ejcts.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Complete left atrial ablation with bipolar radiofrequency☆☆☆

Abstract: Performing the mitral line with bipolar radiofrequency is safe and cost-effective. A complete left atrial ablation with a single bipolar radiofrequency device yields excellent clinical mid-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
19
1
3
Order By: Relevance
“…Recently, Benussi et al demonstrated a complete left atrial ablation with a single bipolar radiofrequency device yielding excellent clinical mid-term results. Freedom from AF was 84% at 6 months and 81% at 1 year [10]. In our study, the overall sinus restoration rate of 85.0% at about 4 years of follow-up, was acceptable in comparison to those of the previous series.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, Benussi et al demonstrated a complete left atrial ablation with a single bipolar radiofrequency device yielding excellent clinical mid-term results. Freedom from AF was 84% at 6 months and 81% at 1 year [10]. In our study, the overall sinus restoration rate of 85.0% at about 4 years of follow-up, was acceptable in comparison to those of the previous series.…”
Section: Discussionsupporting
confidence: 61%
“…It is difficult to ensure a confluent ablation line between the left pulmonary veins and the mitral valve annulus and the tricuspid valve annulus with the bipolar device alone without potentially injuring coronary arteries, and we felt it advisable to use the monopolar pen for these lines for subsequent procedures. Alternative techniques to obtain transmurality to the mitral annulus with only the bipolar device have though been described [22]. In addition, total ablation time between the first 9 and last 18 enrolled patients in the Cardioblate group (success and failure combined) was significantly different with a longer ablation time for the later group (4:03 AE 1:07 vs 5:03 AE 1:12, p = 0.049).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, only 1 patient in the Cardioblate group and 3 patients in the control group were using amiodarone at that time. At discharge, 22 Cardioblate patients (92%) and 13 control patients (52%, p = 0.004 vs Cardioblate group) were prescribed amiodarone. Over time, amiodarone use decreased to 7 patients (29%) in the Cardioblate group and 5 patients (22%) in the control group (CATMOD: group NS, time: p < 0.001, group  time: p = 0.003).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…In 2008, Benussi et al (13) demonstrated the safety and efficacy of a complete bipolar radiofrequency ablation, with superior results compared with those of the unipolar devices. Accordingly, we report here a significant improvement of electrophysiologi- Kaplan-Meier Curves for Combined Event-Free Survival, According to 5 Different Surgical Treatment Arms cal results during the follow-up by simple switching from unipolar to bipolar LA ablation.…”
Section: Discussionmentioning
confidence: 98%